open-japanese-mesh: assigning MeSH UIDs to Japanese medical terms via open Japanese-English glossaries - Ryota Yamada; Yuka Tatieisi (Genomics & Informatics)
The Medical Subject Headings (MeSH) thesaurus is a controlled vocabulary for indexing biomedical documents that is used for document retrieval and other natural language processing purposes. However, although the original English MeSH is freely available, its Japanese translation has a restricted license. We attempted to create an open alternative, and for this purpose we made a script for assigning MeSH UIDs to Japanese medical terms using Japanese-English glossaries. From the MeSpEn glossary and MEDUTX dictionary, we generated a 12,457-word Japanese-MeSH dictionary.